A model for estimation of testicular volume in different age male rats – suitability of various testicular volume calculation formulas for living animals - Lasiene, K.; Kleina, R.; Dabuzinskiene, A.; Gasiliunas, D.; Juodziukyniene, N.; Zilaitiene, B.; Dirziuviene, R. (Polish Journal of Veterinary Sciences, 2025)
A change in testicular volume can indicate decreased male fertility and is useful for comparing spermatogenesis before and after experiments in animals, or before and after treatment of especially valuable domestic breeding animals with pharmaceuticals affecting spermatogenesis, such as antitumor drugs. Various formulae can be used to calculate the volume of living males’ testes. This study examined the suitability of four testicular volume calculation formulas for male Wistar rats of different ages (2-months, 1-year, and 2-years-old) and the changes in testicular volume during 90 days of observation. In 2-months-old rats, the solid ellipsoid triaxial body calculation formula and the prolate ellipsoid formula were most suitable for the calculation of testes’ volume, and the volume of both testes increased very significantly during the 90 days of observation. In 1-year-old rats, the solid ellipsoid triaxial body calculation formula was optimal, and the volume of both testes increased insignificantly. For 2-years-old rats, the solid ellipsoid triaxial body calculation and prolate ellipsoid formulas or their average was recommended, and the volume of both testes decreased slightly during 90 days of observation.
Keywords: calliper; rat; testis; ultrasound; volume